The Performance Of Village Government Apparatus In Improving The Quality Of Public Services In Hamparan Rawang Sub-District, Sungai Penuh City, Jambi Province - Feri Hartanto; Syamsir Syamsir (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This research starts from a variety of problems that have emerged since the promulgation of new village regulations, namely Law Number 6 of 2014 concerning Villages, where strengthening village capacity is being discussed, this certainly demands the performance of village government officials to carry out their duties and functions. The new paradigm of implementing village governance marked by the enactment of Law No. 6 of 2014 concerning Villages has had far-reaching consequences for government institutions at the village level. The purpose of this study was to analyze the performance of the apparatus, the quality of public services, inhibiting factors and supporting factors in providing services in Hamparan Rawang Sub-District, Sungai Penuh City. This study used a qualitative approach in two villages in Hamparan Rawang Subdistrict as research objects. The results of this study indicate that the performance of village officials in improving the quality of public services in Hamparan Rawang Subdistrict has not been maximized and there are still many constrained by lack of budget factors, low quality of human resources, inadequate facilities and pre-facilities, and lack of understanding of village apparatus on IT implementation.